The effects of sports on university students' continuous anger and anger sub-levels - Oksay Oguz; Ahmet Gursel Oguz (Türk Spor ve Egzersiz Dergisi)
In this study, the effect of sports on the anger levels of university students was examined. The study group consisted of 101 male and 99 female students studying at Selçuk University. The continuous anger levels of the individuals who do and do not sports participate in the study were determined by the "Continuous Anger Subscale" of the Continuous Anger - Anger Expression Scale Scale, which was adapted to Turkey by Özer. To analyses data, the independent t-test and ANOVA were conducted. According to the data of 18-20 (40 students), 21-23 (126 students), 24 years and over (34 students); The difference between the two groups who do and do not sports was important for the continuous anger subscale score as a result of two independent sample t tests (p lt;0.05). According to this, the score of the anger subscale is higher than that of the individual who does not perform. The p- value for anger subscale score was found to be significant (p lt;0.05). According to this, the individual who plays sports has a higher score on the subscale of anger than the individual who does not. Sports has played an active role in the suppression of the anger as the university student's constantly raising the level of anger. P value for anger subscale score of independent two-sample T-test for testing whether male and female subjects had significantly different scores of continuous anger subscale scores (p lt;0.05). According to this, the score of the male individual is higher than that of the female anger. It can be said that men can express their anger more easily than women. There was a significant difference between the father professions (p lt;0.05) for the continuous anger subscale scores. The scores of the continuous anger subscale scores of the private sector and the self-employed individuals of the father occupation were the same, while those of the father sector occupation were lower than the scores of the continuous anger subscale of the public sector. These results show that while the anger of the individuals whose father is the private sector and self-employed remains at the same level, the levels of continuous anger of the individuals working for the father in the public sector are found to be low.